Preoperative administration of eculizumab to prevent surgery‐triggered hemolysis during cesarean section with paroxysmal nocturnal hemoglobinuria. Issue 9 (25th July 2018) - Li, Dongping; Wang, Liangcheng; Horiuchi, Isao; Kimura, Shun‐ichi; Chikazawa, Kenro; Kimura, Azusa; Sasaki, Shigetane; Kuwata, Tomoyuki; Takagi, Kenjiro
Key Clinical message: Eculizumab in pregnancy has been reported to be effective in improving outcomes in patients with paroxysmal nocturnal hemoglobinuria. However, a cesarean section may result in surgery‐triggered hemolysis. An additional dose of eculizumab just prior to delivery is an appropriate choice to prevent postoperative hemolysis. Abstract : Eculizumab in pregnancy has been reported to be effective in improving outcomes in patients with paroxysmal nocturnal hemoglobinuria. However, a cesarean section may result in surgery‐triggered hemolysis. An additional dose of eculizumab just prior to delivery is an appropriate choice to prevent postoperative hemolysis.